Advances in Automotive Technologies Select Proceedings of ICPAT 2019 - Nalim, M. Razi.; Vasudevan, R.; Rahatekar, Sameer; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book contains selected papers from the International Conference on Progress in Automotive Technologies (ICPAT) 2019. The contents focus on several aspects of the automobile industry from design to manufacture, and the challenges involved therein. The book covers latest research trends in the automotive domain including topics such as aerodynamic design, vehicle sensors and electronics, engine combustion modeling, noise and vibration in vehicles, electric and hybrid vehicles, automotive tribology, and battery and fuel cell technologies. The book highlights the use of emerging technologies to tackle the growing environmental challenges. This book will be of interest to students, researchers as well as professionals working in automotive engineering and allied fields.
CFD Analysis of Automotive Radiators -- Ejector- Vapour Compression Hybrid Air Conditioning System for Automotives: System configuration and Analysis -- Investigation of the Combined Effect of Perforated Tube, Baffles and Porous Material on Acoustic Attenuation Performance -- Semi-autonomous Vehicle Transmission and Braking Systems -- Comparison of gaseous and liquid fuel cells for automotive applications.
Keywords: Automotive engineering; Engineering design; Tribology; Corrosion and anti-corrosives.; Coatings; Manufactures; Automotive Engineering; Engineering Design; Tribology, Corrosion and Coatings; Manufacturing, Machines, Tools, Processes